2016
DOI: 10.1016/j.ijsu.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Topical fibrin sealant versus intravenous tranexamic acid for reducing blood loss following total knee arthroplasty: A systematic review and meta-analysis

Abstract: Our meta-analysis suggests that intravenous administration of TXA for patients undergoing TKA may reduce blood-transfusion requirements and maintain higher hemoglobin levels compared with topical application of FS in the early postoperative period. There were no significant differences in total calculated blood loss and prevalence of complications between the two groups. However, owing to the variation of included studies, no firm conclusions can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…(*)Tranexamic acid is recognized as a valuable innovation under a fast-track THA pathway [75]. Its effectiveness in conventional TKA had also been largely demonstrated [114, 134], supporting it to be a valuable innovation in fast-track TKA too.Topical fibrin sealants (TFS)A meta-analysis on TKA suggests the administration of intravenous TXA to dominate on TFS [135], whose effectiveness and cost-effectiveness are debatable [136, 137]. The eventual use of TFS in revision surgery makes them irrelevant for fast-track pathways, which are dedicated to primary intervention.(Intraoperative) cell salvageA meta-analysis on 43 trials show perioperative (intra- and post-) cell salvage to reduce blood loss in both THA and TKA [138].…”
Section: Resultsmentioning
confidence: 99%
“…(*)Tranexamic acid is recognized as a valuable innovation under a fast-track THA pathway [75]. Its effectiveness in conventional TKA had also been largely demonstrated [114, 134], supporting it to be a valuable innovation in fast-track TKA too.Topical fibrin sealants (TFS)A meta-analysis on TKA suggests the administration of intravenous TXA to dominate on TFS [135], whose effectiveness and cost-effectiveness are debatable [136, 137]. The eventual use of TFS in revision surgery makes them irrelevant for fast-track pathways, which are dedicated to primary intervention.(Intraoperative) cell salvageA meta-analysis on 43 trials show perioperative (intra- and post-) cell salvage to reduce blood loss in both THA and TKA [138].…”
Section: Resultsmentioning
confidence: 99%
“…However, when taken into consideration the routine use of erythropoietin and fibrin sealant, it should balance its large costs. [ 6 8 ] Compared with fibrin sealant, TXA performs equal hemostatic effects with less costs. [ 8 , 9 ] Molloy et al [ 10 ] conducted a randomized controlled trials (RCTs) comparing topical fibrin spray to intravenous (IV) TXA demonstrated comparable blood loss control but also showed that the cost of topical fibrin spray was $585.00 compared to $6.00 with IV TXA.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses offer contradictory conclusions as to whether fibrin sealant reduces total blood loss; however, there may be a reduction in drain output and transfusion rate without an increased risk of complications 70. Fibrin sealant is not as effective as tranexamic acid at reducing blood loss71 and given the high additional cost, the role of fibrin sealant in a multimodal blood management algorithm is uncertain.…”
Section: Intraoperativementioning
confidence: 99%